2008
DOI: 10.1002/jpln.200700049
|View full text |Cite
|
Sign up to set email alerts
|

How relevant is recalcitrance for the stabilization of organic matter in soils?

Abstract: Traditionally, the selective preservation of certain recalcitrant organic compounds and the formation of recalcitrant humic substances have been regarded as an important mechanism for soil organic matter (SOM) stabilization. Based on a critical overview of available methods and on results from a cooperative research program, this paper evaluates how relevant recalcitrance is for the long-term stabilization of SOM or its fractions. Methodologically, recalcitrance is difficult to assess, since the persistence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
359
2
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 626 publications
(409 citation statements)
references
References 138 publications
22
359
2
8
Order By: Relevance
“…This result was of high importance, supporting the largely anecdotal evidence that shrub dominated the areas across the basin study area that is used to be dominated by grasses [Buffington and Herbel, 1965]. At the Los Piños sites, due to the similarities between grama grass and juniper n-alkane signatures, there was a degree of difficulty in determining between sources; based upon n-alkane signature, a problem was previously experienced when using n-alkane signatures alone [Marschner et al, 2008;Gocke et al, 2011]. However, the use of n-alkane signatures from piñon and combined with the δ 13 C values of both piñon and juniper demonstrated that the same trends transcend to the mountainous, grassland to piñon-juniper transition [Wilcox et al, 2003b].…”
Section: Change In the Source Of C Over Vegetation Transitionssupporting
confidence: 63%
“…This result was of high importance, supporting the largely anecdotal evidence that shrub dominated the areas across the basin study area that is used to be dominated by grasses [Buffington and Herbel, 1965]. At the Los Piños sites, due to the similarities between grama grass and juniper n-alkane signatures, there was a degree of difficulty in determining between sources; based upon n-alkane signature, a problem was previously experienced when using n-alkane signatures alone [Marschner et al, 2008;Gocke et al, 2011]. However, the use of n-alkane signatures from piñon and combined with the δ 13 C values of both piñon and juniper demonstrated that the same trends transcend to the mountainous, grassland to piñon-juniper transition [Wilcox et al, 2003b].…”
Section: Change In the Source Of C Over Vegetation Transitionssupporting
confidence: 63%
“…New observations show these to be only marginally important for organic matter cycling 12,13 . Furthermore, loose use of the term 'recalcitrance' has significantly confused the discussion in the past.…”
Section: Recent Insights Into Carbon Cyclingmentioning
confidence: 99%
“…However, using compound-specific isotopic analysis, molecules predicted to persist in soils (such as lignins or plant lipids) have been shown to turn over more rapidly than the bulk of the organic matter ( Fig. 1) 12,[15][16][17] . Furthermore, other potentially labile compounds, such as sugars, can persist not for weeks but for decades.…”
Section: Molecular Structure and Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a talk considering the importance of recalcitrance as a stabilization mechanism for soil organic matter, Bernt Marschner reported that there was little evidence for it, except in the case of black carbon and fossil carbon (see : Marschner et al 2008). The recalcitrance of black carbon was further discussed by both Michael Schmidt (see: Preston and Schmidt 2006) and Johannes Lehmann (see: Nguyen et al 2008), with the latter providing evidence that even here interactions with minerals may play an important role in retarding degradation.…”
Section: Conference Highlightsmentioning
confidence: 99%